Upaya Pencegahan Demam Berdarah Dengue (DBD) di SDN 16 Kecamatan Pontianak Timur dengan Produk Lilin Aromaterapi Serai (Cymbopogon citratus): Prevention of Dengue Hemorrhagic Fever (DHF) in SDN 16 East Pontianak District with Lemongrass (Cymbopogon citratus) Aromatherapy Candle - Anjani, Ayu Paramitha; Olvi, Tea Gilda Dara Mula; Ananda, Ersa; Erdatama, Fiqry; Kurniawan, Hadi; Kusharyanti, Indri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Dengue Hemorrhagic Fever is a disease caused by a virus by Aedes aegypti mosquitoes. West Kalimantan is experiencing an increasing trend in dengue cases, with data of 4,304 incident cases and 48 deaths, most recently in the 43rd week of October 2023, so handling activities are needed to reduce the number of dengue cases. Kuliah Kerja Nyata is an action-based community service program currently being implemented at Sekolah Dasar Negeri 16, Banjar Serasan Village, East Pontianak District, Pontianak City. This text aims to increase knowledge and insight about dengue fever and ethnomedicine among students and teaching staff, increase awareness, look for alternative prevention methods, and be aware of the importance of preventing dengue fever. The method is implemented in the form of outreach, education, and demonstration. An evaluation was carried out to determine the participant's level of understanding through pretest, post-test, and questionnaires. The results obtained were that there was an increase in students' understanding of dengue fever based on an increase of 13.29% from pretest to post-test scores, and 59.61% of respondents stated that the activities had a positive impact on respondents.